2013
DOI: 10.1136/bcr-2013-010374
|View full text |Cite
|
Sign up to set email alerts
|

Renal arteriovenous malformation: an unusual cause of recurrent haematuria

Abstract: A 54-year-old woman presented with gross painless haematuria. Initial workup showed no abnormality except mild hydronephrosis on CT scan. Cystoscopy and retrograde pyelography did not find any gross lesion and her urine cytology was also negative. She had recurrent haematuria so her CT was reviewed with the radiologist with clinical suspicion of arteriovenous malformation (AVM) which was suggested by relatively increased contrast density in the hemiazygous vein and renal vein in the arterial phase. She underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Both of the present patients had type III AVMs in which no large aneurysms are formed; therefore, it was difficult to make a diagnosis with CECT. Several cases of renal AVMs have been reported that could not be diagnosed by CT examination or ultrasonography but were diagnosed by angiography, and most of them were caused by an abnormal vascular network corresponding to a type III AVM 3–6 . Color Doppler ultrasonography is inexpensive and the preferred initial diagnostic method for evaluation of the kidneys, and specific findings such as colored mosaic patterns can lead to the diagnosis of type I and II AVMs 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Both of the present patients had type III AVMs in which no large aneurysms are formed; therefore, it was difficult to make a diagnosis with CECT. Several cases of renal AVMs have been reported that could not be diagnosed by CT examination or ultrasonography but were diagnosed by angiography, and most of them were caused by an abnormal vascular network corresponding to a type III AVM 3–6 . Color Doppler ultrasonography is inexpensive and the preferred initial diagnostic method for evaluation of the kidneys, and specific findings such as colored mosaic patterns can lead to the diagnosis of type I and II AVMs 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, technical failure was mainly attributed to the existence of multiple proximal feeding arteries, and similar cases were also reported in several previous studies. 2,4,14 The difficulty in this type of patient is that trying to embolize the multiple proximal feeders will cause a large area of renal parenchyma infarction, leading to loss of renal function and severe postoperative pain. The current opinion is that even partial embolization may occlude some risk branches and reduce blood pressure in the rAVMs, which may lead to clinical success or reduce the severity of recurrent hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…The major diagnostic challenge physicians face in identifying RAVMs with POCS is distinguishing the dilated hypoechoic renal collecting system caused by obstruction versus the hypoechoic vascular structures found in RAVMs. 2,3 RAVMs are deceptive in that, like obstructive hydronephrosis, they may present with gross hematuria. Since hematuria can be a symptom of several other conditions, including bladder cancer and ureteral calculi, further imaging is often required to determine the etiology of the symptom.…”
Section: Discussionmentioning
confidence: 99%